2011
DOI: 10.3937/kampomed.62.727
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen Cases of Appetite Loss Treated with Shoyogan

Abstract: Shoyogan is a Kampo prescription described in the Junqui Yaolue. Few cases have been reported using this medicine. This time, we prescribed shoyogan for 14 patients who suffered from severe appetite loss. We had positive outcomes as follows. We administered shoyogan to 8 patients with malignant disease. Six of them suffered from lung cancer. Shoyogan was effective in these patients. Shoyogan was not effective for the other 2 patients, with bile duct carcinoma and malignant lymphoma. The dietary intake was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Nevertheless, approximately 2 h after oral shoyogan, her appetite improved; subsequently, her general condition strikingly improved and she survived for a further 2 months. Subsequently, we reported clinical efficacy in a study of 14 anorexic patients with malignant and nonmalignant disease [3]. In the present, larger-scale study, we have shown that shoyogan improves dietary intake of severely anorexic patients with a wide range of malignant and nonmalignant diseases.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Nevertheless, approximately 2 h after oral shoyogan, her appetite improved; subsequently, her general condition strikingly improved and she survived for a further 2 months. Subsequently, we reported clinical efficacy in a study of 14 anorexic patients with malignant and nonmalignant disease [3]. In the present, larger-scale study, we have shown that shoyogan improves dietary intake of severely anorexic patients with a wide range of malignant and nonmalignant diseases.…”
Section: Discussionsupporting
confidence: 51%
“…We have shown that shoyogan improved dietary intake of a patient in the terminal stage of pulmonary cancer, leading to transient improvement of general condition [2]. We also reported that shoyogan improved the dietary intake of 14 severely anorexic patients with malignant or non-malignant disease [3].…”
Section: Introductionmentioning
confidence: 79%